Pengaruh Senam Ergonomik terhadap Penurunan Tekanan Darah Penderita Hipertensi di Posyandu Tinggede Selatan - Susanto, Denny; Purwiningsih, Sri; Kantohe, Imelda (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
Hypertension is one of the non-communicable diseases that often occurs in society and is known as a "silent killer" because its symptoms are often not recognized. Data shows that the prevalence of hypertension in Central Sulawesi is quite high. Non-pharmacological management such as ergonomic gymnastics is a potential alternative in lowering blood pressure in hypertension patients. This study aims to analyze the effect of ergonomic gymnastics on reducing blood pressure in hypertension patients at the Tinggede Selatan Posyandu in the Tinggede Health Center working area. This study uses a quantitative approach with a pre-experimental one group pretest-posttest design. The research sample consisted of 35 hypertension patients taken using the total sampling technique. The intervention in the form of ergonomic gymnastics was given twice a week for 2 weeks. Before the intervention, 21 respondents (60.0%) were in the stage 1 hypertension category and after the intervention, there was a significant decrease in blood pressure in the prehypertension category of 21 respondents (60.0%). The results of statistical tests using the Wilcoxon test were obtained with a p value = 0.000 (<0.05). Ergonomic gymnastics has been proven to have a significant effect in lowering blood pressure in hypertensive patients. Ergonomic gymnastics can be used as an alternative non-pharmacological therapy recommended for hypertensive patients, and is recommended to be carried out routinely and in a structured manner as part of a health program at the integrated health post.